2015
DOI: 10.18549/pharmpract.2015.04.644
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of pharmacists, students and the general public on mHealth applications for medication adherence

Abstract: Background:During recent years mobile technology has developed tremendously and has infiltrated the healthcare field. Mobile healthcare (mHealth) applications, or apps, may be used to support patient adherence to medication thus promoting optimal treatment outcomes and reducing medication wastage.Objective:This study shall consider the opinions of United Kingdom (UK) based pharmacists, pharmacy undergraduates and members of the general public towards the use of mHealth apps to promote adherence to prescribed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
(61 reference statements)
6
26
0
2
Order By: Relevance
“…Currently, internet becomes a substitute resource for those information. Similar with our study, previous studies showed that men in the older cohort (age >65 years) used the internet less frequently than the younger and also felt less comfortable using the internet [13],while younger participants (age < 44 years) were reported to be positive to use mHealth applications for medication adherence compared to the older participants [14]. However, we do find out that about 30% of the patients over 65 years old use the internet to get health information.…”
Section: Discussionsupporting
confidence: 89%
“…Currently, internet becomes a substitute resource for those information. Similar with our study, previous studies showed that men in the older cohort (age >65 years) used the internet less frequently than the younger and also felt less comfortable using the internet [13],while younger participants (age < 44 years) were reported to be positive to use mHealth applications for medication adherence compared to the older participants [14]. However, we do find out that about 30% of the patients over 65 years old use the internet to get health information.…”
Section: Discussionsupporting
confidence: 89%
“…The authors hope that this paper encourages others to consider undertaking a similar project. The key findings are similar to those reported elsewhere in relation to usefulness as an educational tool at undergraduate level for medical and pharmacy students (16)(17)(18) and to support clinical decision-making in practice (19)(20)(21)(22)(23) .…”
Section: Discussionsupporting
confidence: 87%
“…The senior pharmacists stated that the technology is beneficial to combine pharmacy practice with apps. However, they also mentioned that the apps are complex and the only 2.4% of pharmacists stated that mobile health apps could be used in pharmacy practices [28]. In the present study, the applicability of mobile health apps to the pharmacy practice with the developing technology was found to be high in the questionnaire applied to the students of pharmacy.…”
Section: Discussionmentioning
confidence: 51%